2002
DOI: 10.1210/en.143.8.2995
|View full text |Cite
|
Sign up to set email alerts
|

Eating Elicited by Orexin-A, But Not Melanin-Concentrating Hormone, Is Opioid Mediated

Abstract: Melanin-concentrating hormone (MCH) and orexin-A are orexigenic peptidergic neurotransmitters produced primarily in the lateral hypothalamus. Because two other hypothalamic peptides, neuropeptide Y and agouti-related peptide, increase food intake by a mechanism that depends on activation of opioid receptors, we assessed whether MCH or orexin-A also elicits food intake via opioid receptor activation. A dose of naloxone (0.3 mg/kg, ip) that had no effect on its own reduced the acute orexigenic effect of third ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 0 publications
2
71
0
1
Order By: Relevance
“…Clegg et al reported that i.c.v. injection of orexin-A and -B increased food intake for 1 h, and that the effects were inhibited completely by intraperitoneal injection of naloxone, an antagonist of the opioid receptor (2). Furthermore, i.c.v.…”
Section: Resultsmentioning
confidence: 93%
“…Clegg et al reported that i.c.v. injection of orexin-A and -B increased food intake for 1 h, and that the effects were inhibited completely by intraperitoneal injection of naloxone, an antagonist of the opioid receptor (2). Furthermore, i.c.v.…”
Section: Resultsmentioning
confidence: 93%
“…MCH administration stimulated the consumption of a high-fat diet equally to that of low-fat diet. Further, the effect of MCH on food intake was found to be independent of the opioid system, which is thought to be involved in signaling the relative palatability of food (Clegg et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the dopaminecontaining neurons in the midbrain VTA, which has a high density of -opioid receptors, play a critical role in the rewarding effects of -opioids. It has been reported that endogenous opioids are needed for orexin-induced feeding (Clegg et al, 2002). It is of interest to note that prepro-orexin knock-out mice develop attenuated morphine-induced physical dependence and withdrawal (Georgescu et al, 2003), suggesting a possible interaction between orexins and opioids.…”
Section: Discussionmentioning
confidence: 99%